Imposition, adoption, and resistance in Lynne Kutsukake’s The Translation of Love: A postcolonial approach - Bhakti Satrio Nugroho; Muhammad Arif Rokhman (Universitas Islam Sultan Agung, 2020)
This paper, which is under Transnational American Studies and Postcolonial Studies, aims to analyze a process of creating a colonial culture which involves cultural imposition, adoption, and resistance in Lynne Kutsukake’s The Translation of Love. This novel depicts postwar Japanese society that lives under American power after the end of World War II while undergo kyodatsu (the period of an economic, social and moral crisis caused by the war). This paper is a qualitative research that utilizes three theories, including cultural imposition, mimicry and symbolic resistance. The finding, shows the devaluation of Japanese cultural identity which used to oppose the claim of “otherness” by the West. In cultural imposition, the United States manages to impose American ideology, language, lifestyle, customs and fashion through various ways such as media, social interaction, social obligation and school curriculum. Meanwhile, in cultural adoption, postwar Japanese adopt American cultures in which it asserts that there is a shift of postwar Japanese cultural orientation that tends to celebrate American culture as a “sign of liberation”. Then, in symbolic resistance, postwar Japanese resistance toward the United States as the occupying power is only manifested in subversive everyday gestures which include covert and overt form. In short, this analysis shows that, during U.S. occupation, postwar Japan only becomes “a pawn” in the United States’ postwar plan for global dominance by rebuilding a new Japanese society under American influence.